The Effect of Physical Education Instructional Media on Long Jump Learning Outcomes - Ritonga, Doris Apriani; Verawati, Indah; Damanik, Saipul Ambri (JTP - Jurnal Teknologi Pendidikan, 2025)
This research aims to see the effect of the use video on physical Education learning outcomes for state high school students in Medan City. The method used in this research is an experimental method using the Pre Experimental Design research type. The sample in this research was state high school students in Medan City, totaling 25 students. Data analysis in this study used SPSS (version 25). The results of this research show that the data normality test shows that the pretest and posttest significance values ​​are greater than 0.05, so it can be concluded that the data is normally distributed. The significance value homogeneity test is greater than 0.05, so it can be concluded that the data is homogeneously distributed. The T test between the pretest and posttest output of the "paired sample test" above, shows the sig value. (2 tailed) is 0.00 < 0.05, then HO is rejected and Ha is accepted. The average student learning result in the pretest is 67.32 while in the posttest it is 79.30 with a significance test of the T Test (2 tailed) < 0.05, so HO is rejected and Ha is accepted. State High School in Medan City.